Learning in the service environment: the influence of diversity climate. Issue 4 (11th July 2016) - Guchait, Priyanko; Madera, Juan; Dawson, Mary
Abstract : Purpose: – The purpose of this paper is to examine how diversity climate in service organizations influence employee learning behavior. Additionally, the study examined the mediating effects of psychological safety and communication satisfaction between diversity climate and learning behavior. Design/methodology/approach: – Data were collected from 128 hotel and lodging managers by administering survey questionnaires. The dual mediational model was tested using the mediation test suggested by Preacher and Hayes (2008). Findings: – Results indicated that when managers perceived a positive diversity climate they also reported high engagement in learning behavior. Additionally, the study found the mediating effects of psychological safety and communication satisfaction. Originality/value: – The importance of learning behavior has been noted by researchers and practitioners because of its influence on service performance. Learning behavior is especially important in complex, error prone, and fast changing businesses like the services industry. This research contributes to the existing body of research by examining the influence of diversity climate on learning behavior, which has not been investigated empirically in the literature. The current research not only makes a significant contribution to the learning and diversity literature, but also informs practitioners how learning behavior can be increased and how diversity climate can be created in within service organizations, in particularly hospitality.